Building inter-storey drift under pseudo dynamic load - Pang, Hui Er (2023)
Earthquake is the most destructive natural disaster which causes fatalities and destruction globally. Malaysia is considered a region with a low seismicity profile. Earthquakes that happened in neighbouring countries such as Indonesia and Philippines induced impacts and the earthquake tremors may affect buildings in Malaysia. Viscous damper systems have been introduced in this research and potentially enhance the seismic resistance of the building. The main focus of this research is assessing the inter-storey drift performance and mode shape of the scaled reinforced building with and without dampers. A 1:8 downscaled model of 1 bay 3-storey reinforced concrete structure was constructed based on critical parts of a high school building’s perimeter structural skeleton for the shaking table’s dynamic load test. The model specifications were acquired by applying Similitude Theory and Buckingham’s Pi Theorem in order to establish the correlation between the prototype and downscaled model. Failure mode and damage mechanism of the scaled model under different levels of earthquake intensity found that the inter-storey drift of the scaled model is huge when the ground is having large movement with low aggressiveness. On the other hand, when the earthquake's intensity increases, the structural movement was found to reduce gradually with intense vibration such as primary wave. The structure was found to have a higher translation mode of oscillation from single curvature to double curvature when the ground acceleration was getting intense. Three brands of viscous dampers were tested and compared in this study as well. The results showed that all viscous dampers are able to reduce the building inter-storey drift. The breakthrough of this research is the finding of the scaled models' overall rooftop displacements are lowered by 45%, 63% and 34% under different intensities of ground movement with the installation of the APIDO, SKK and ESPADA viscous dampers, respectively. Hence, the novelty of this research is that the APIDO viscous damping system is found to be the most suitable for absorbing large displacement, while SKK viscous damping system is suitable for building lateral displacement generated under intense ground vibration.